Investigation on university pre-service teachers’ perceptions of the existence and future mathematics for 21st century skills in a Tanzanian context - Emmanuel Deogratias; Aziza J. Iddi (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
The pursuit of understanding the role of mathematics in society has been a longstanding concern in mathematics education, dating back to ancient civilizations such as Greece and Egypt, where mathematics was valued for its problem-solving and practical applications. Recently, the National Council of Teachers of Mathematics (NCTM) has emphasized the need for mathematics education to prepare students for an increasingly complex and technologically driven world. Within this historical context, this quantitative study investigated the views of 91 University mathematics pre-service teachers (PSTs) regarding the existence and future of mathematics. The study used a questionnaire to collect data, which was then analyzed using Statistical Packages for Social Sciences (SPSS) and presented in tables, pie charts, and bar charts. The findings suggest that PSTs can provide reasons for the existence of mathematics, reasons for learning mathematics, and ideas about how mathematics should be taught and learned in the 21st century. The study's results have implications for teaching and learning mathematics, highlighting the importance of understanding the historical development of mathematics, as well as its current and future applications, to prepare PSTs to teach mathematics in a way that is relevant and engaging to meet the challenges of the 21st century.